The transformation of waqf in Turkey from the Ottoman to the contemporary period - Ahmad Wira,; Meirison,; Elfia, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper aims to provide an overview of the existence of waqf in Turkey and the changes that occurred during the Ottoman Empire, which for a long time sustained the existence of Islamic civilization, including community service in the fields of worship, education, social and military. Even though Turkey has been completely secularized, waqf still exists in various forms. Using literary methods, historical qualitative approaches, and descriptive analysis, the researchers attempt to reveal the conditions and types of waqf in Turkey during the Ottoman period and the modern era, namely after the fall of the Ottoman Empire. In general, the researchers found that waqf in Turkey was used for humanitarian purposes, both for Muslims and non-Muslims, and animals might also benefit from the waqf. In the post-Ottoman Turkish period, waqf emerged in other forms, such as special waqf to deal with earthquakes and natural disasters, as well as to help widows and children of war victims. Sufi orders also played a role in the development of waqf, which avoided direct conflict with the secular government of the time of Kemal Atatürk and his supporters. Sufi orders lived to develop Waqf in community services, hospitals, education, and other social activities— expansion of sufi waqf in the Balkans.